2015
DOI: 10.1002/pen.24177
|View full text |Cite
|
Sign up to set email alerts
|

Phase structure and mechanical properties of PP/EPR/CaCO3 nanocomposites: Effect of particle's size and treatment

Abstract: Calcium carbonate (CaCO 3 ) reinforced polypropylene/ ethylene propylene rubber (PP/EPR) copolymer composites for automotive use were developed by means of extrusion and injection molding process. Three kinds of CaCO 3 (stearic acid treated and untreated) nanoparticles and microparticles were used as fillers. The influence of stearic acid, particle size, and filler content on the state distribution and morphology were investigated by SEM and rheological measurements. Two different morphologies were observed: E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Good agreement was achieved between the experimental and theoretical results, which provided new ideas for material design. Elloumi and co‐workers investigated the effects of particle size and filler treatment of CaCO 3 on the properties of PP/EPR/CaCO 3 composites. They found that improvements in the notched impact strength could be obtained by nano‐CaCO 3 and that the treated particles had a tendency to form complicated structures with EPR, which could attain better impact strength.…”
Section: Introductionmentioning
confidence: 99%
“…Good agreement was achieved between the experimental and theoretical results, which provided new ideas for material design. Elloumi and co‐workers investigated the effects of particle size and filler treatment of CaCO 3 on the properties of PP/EPR/CaCO 3 composites. They found that improvements in the notched impact strength could be obtained by nano‐CaCO 3 and that the treated particles had a tendency to form complicated structures with EPR, which could attain better impact strength.…”
Section: Introductionmentioning
confidence: 99%
“…Due to nanometer size of these particles, their physicochemical characteristics differ significantly from those of molecular and bulk materials. Nanoparticle reinforced polymers, synergistically combine the properties of both the host polymer matrix and the discrete nanoparticles [16][17][18]. Epoxy nanocomposites exhibit a wide range of positive characteristics, such as dielectric behaviors, thermal stability properties, good corrosion resistance, mechanical performance, and excellent tribological properties [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The variation of the coefficient of friction under different operating conditions is a very important issue. The coefficient of friction of nanocomposites can be affected by many factors such as mechanical behaviors, surface topography, particle size, particle surface treatment, and contents of filler …”
Section: Introductionmentioning
confidence: 99%
“…[38] The variation of the coefficient of friction under different operating conditions is a very important issue. The coefficient of friction of nanocomposites can be affected by many factors such as mechanical behaviors, surface topography, particle size, [39][40][41] particle surface treatment, [42,43] and contents of filler. [34] Therefore, effect of nanosilica contents, particle sizes, and surface treatments (polydimethylsiloxane (PDMS)-treated and dimethyldichlorosilane (DDS)-treated nanosilica particles) on mechanical, thermal, and physical properties of highly filled nanosilica-polybenzoxazine composites was examined in this research.…”
Section: Introductionmentioning
confidence: 99%